Cancer stem cell–immune cell crosstalk in breast tumor microenvironment: a determinant of therapeutic facet - Guha, Aishwarya; Goswami, Kuntal Kanti; Sultana, Jasmine; Ganguly, Nilanjan; Choudhury, Pritha Roy; Chakravarti, Mohona; Bhuniya, Avishek; Sarkar, Anirban; Bera, Saurav; Dhar, Sukanya; Das, Juhina; Das, Tapasi; et al. (Frontiers in Immunology, 2023)
Breast cancer (BC) is globally one of the leading killers among women. Within a breast tumor, a minor population of transformed cells accountable for drug resistance, survival, and metastasis is known as breast cancer stem cells (BCSCs). Several experimental lines of evidence have indicated that BCSCs influence the functionality of immune cells. They evade immune surveillance by altering the characteristics of immune cells and modulate the tumor landscape to an immune-suppressive type. They are proficient in switching from a quiescent phase (slowly cycling) to an actively proliferating phenotype with a high degree of plasticity. This review confers the relevance and impact of crosstalk between immune cells and BCSCs as a fate determinant for BC prognosis. It also focuses on current strategies for targeting these aberrant BCSCs that could open avenues for the treatment of breast carcinoma.